Tooth Bleaching: Types and Procedure with their Contentious Effects A Literature Core - Sarah Hanif, Ayesha Iqbal, Suraiya Hirani, Faiza Ubaid, Ali Raza, Tasneem Ali (Pakistan Journal of Medical & Health Sciences, 2022)
Imitation of smile aesthetics and analysis, is an initial step for dental bleaching, hence it is significant that the dentist/dental hygienist identifies how to analyze the root causes of color change and to specify whitening before suggesting the suitable dental procedure. With the high-tech advancement, dental bleaching techniques have arose to assist its use and provide comfort, safety and reduction in time, in the performance of the technique. The conservative means of external dental whitening is with hydrogen peroxide (photo activated or not) or carbamate. However, dental sensitivity is frequently complained by patients by the home and office whitening procedures. There is an innovative bleaching application in the market without the use of these bleaching gels, as a consequence decreasing post-treatment sensitivity. Such a suggestion elucidates, replacing bleaching agent by ultraviolet light. The object of this literature review is to enlighten the determining factors that affect the final satisfactory results of the different techniques and explains a general overview, permissible to reach a treatment conclusion based on evidence. Keywords: tooth whitening, tooth bleaching, types of tooth bleaching, procedures of tooth whitening